Too secret too long - "Pincher, Chapman" (New York, 1984)
'Was there a Soviet mole in the highest reaches of the British secret service? British journalist Chapman Pincher thinks so, and he thinks it was Roger Hollis, who was head of MI-5 from 1956 to 1965. Pincher takes some 600 pages to weave his web of circumstantial evidence, and in doing so takes us once again through all the now familiar but still engrossing cases of British spy-traitors-Burgess, Maclean, Philby, Blunt, George Blake, Gordon Lonsdale (the list is very long). The evidence is indeed suggestive, but Sir Roger has been dead since 1973.
Keywords: Espionage - Great Britain - History - 20th century